Hagfish slime gland thread cells. II. Isolation and characterization of intermediate filament components associated with the thread (The Rockefeller University Press, 1984)
The slime glands of hagfish have two major cell types, gland thread cells (GTCs) and gland mucous cells (GMCs), both of which upon contact with water contribute to the formation of an abundant quantity of viscous mucus. In previous studies we reported a method for the isolation of GTCs and showed that each ellipsoidal thread cell normally contains a single tapered thread which is uniquely coiled into a space- saving conformation and occupies most of the cell volume. Subsequently, the developing thread was found to consist mainly of intermediate filaments (IFs) aligned in parallel not only to one another but also to a far fewer number of interspersed microtubules (see accompanying paper). In the present report, urea extracts of GTCs were purified and characterized to establish the properties of thread components. One major (alpha) and two minor (beta, gamma) components prepared by anion exchange chromatography were shown to have similar apparent molecular weights of 63,500 +/- 500 daltons but different isoelectric pH values (alpha, 7.56; beta, 5.67; gamma, 5.31). Although the amino acid content of alpha differed significantly from beta and gamma, each of the three was highest in Gly, relatively high in Glx, Ser, Thr, Asx, Ala, Val, and Leu, and relatively low in Cys/2 and Trp. The amino acid compositions of beta and gamma were very similar, and only beta showed evidence of carbohydrate. The threonine content of the alpha component was higher than has been reported for IFs of different origin, and the high content of hydroxyamino acids (18, 19 residues per 100) in alpha, beta, and gamma has been approached only by several IF polypeptides from human or bovine epidermal keratins. Mixtures of the purified components formed 9-11-nm filaments in vitro. The results indicate that the hagfish thread cell is a rich source of IFs, which have a structure that facilitates formation of macrofibrils within the cell.